Analysis of a building-mounted wind-solar hybrid power system in urban residential areas: The case study of Istanbul - (:unkn) unknown (Springer, 2021)
In cities, buildings play an important role in electricity consumption and are one of the central problems of global warming. Therefore, buildings are good alternatives for micro-power generation facilities. In this paper, Göztepe, Istanbul is selected as a pilot region in Turkey. Solar and wind energy potential of this region was examined in order to study the feasibility of a hybrid wind-solar system. Technical analysis and cost analysis are performed for the electricity demand of the building. A computational fluid dynamics program is used to determine the most appropriate place for installation of the wind turbines on the top of the building. HOMER software is used to simulate and analyzing the performance of system. © Springer Nature Singapore Pte Ltd. 2021.
Keywords: Building-mounted; CFD; HOMER; Hybrid system; Residential areas; Solar energy; Wind power